Promoting Economic Independence Economic Independence through Digital Technology and Operational Management for Improved Product Competitiveness - Marina, Ida; Harti, Adi Oksifa Rahma; Dahtiar, Agi; Fernanda, Billy Adrian; Hasanah, Hanna Ariah (Pascasarjana Universitas Mataram, 2024)
This community service program aims to increase the capacity and sustainability of Cilembu yam MSME players in Cilembu Village through structured training and mentoring. Activities began with six initial meetings involving 30 participants, mostly women aged 56-80 years old with basic education backgrounds. The training focused on digital technology and operational management, as well as new product development. Evaluation showed that the training successfully increased the use of digital technology from 72.26% to 85%, with a significant increase in the adoption of e-commerce platforms. Participation from younger age groups also increased from 13% to 20%, demonstrating the program's success in attracting the younger generation. Challenges related to productivity and marketing decreased, with productivity issues falling from 61.51% to 40% and marketing issues from 54.19% to 35%. The effectiveness of the training increased, with 90% of participants able to apply the training materials in their businesses. Support and communication from the implementation team was also rated as excellent, with responsiveness increasing to 95%. In conclusion, the program had a significant positive impact, but there are still challenges that need to be addressed in terms of productivity and marketing. It is recommended to focus on e-commerce technology capacity building, capital development, and product innovation, as well as strengthening ongoing mentoring to ensure the sustainability and development of MSMEs in the future